ALGORITMA AES128-CBC (ADVANCED ENCRYPTION STANDARD) UNTUK ENKRIPSI DAN DEKRIPSI BERKAS DOKUMEN PT. ADIARTA MUZIZAT - Mohammad Rezza Fahlevvi; Dhita Satria Aprilliana Putra; Wahyu Ariandi (Journal of Innovation And Future Technology, 2025)
The rapid advancement of digital technology has increased concerns about data security, especially in document storage and transmission. PT. Adiarta Muzizat, a logistics company, has experienced multiple data breaches, highlighting the need for a more secure encryption method. This study focuses on implementing the Advanced Encryption Standard (AES) 128-bit with Cipher Block Chaining (CBC) mode to enhance document security. The research follows the Rational Unified Process (RUP) methodology, comprising four phases: inception, elaboration, construction, and transition. The encryption and decryption processes were tested on various document formats, evaluating performance in terms of speed, file size differences, and resistance to brute-force attacks. The results indicate that AES-128-CBC successfully prevents unauthorized access, as encrypted documents remain unreadable without the correct decryption key. Additionally, security tests using Crackstation revealed that AES-128-CBC is significantly more resilient compared to MD5 and SHA-256. The study concludes that implementing AES-128-CBC enhances document confidentiality, ensuring data integrity and security. Future research could explore AES-256 or blockchain integration for improved security and efficiency.